Ang pilosopiya at si Roque J. Ferriols, SJ - Calano, Mark Joseph T. (2015)
The paper articulates the relationship between philosophy, Eros, and the Filipino Jesuit priest Roque J. Ferriols. As a way of life, philosophy is related to three Greek words (thaumazein, aesthesis, and logos) and is the desire for the hen panta (one-in-all). The paper then describes the life of the philosophos by refferring to the image of Eros and the character of Socrates in Plato's Symposium. It ends by identifying the philosophical project of Ferriols with the quest of the philosophos. It argues for meron as the articulation/inarticulation of a universal truth, of what is really real, and as the proper concern of the philisopher.
Keywords: Philosophy